Implementation of Food Sanitation and Hygiene in Families with Diarrhea - Ferizal Masra; Suami Indarwati; Linda Barus (Sociometry Journal of Social Science, Art and Humanity, 2022)
Diarrhea is still a public health problem in developing countries such as Indonesia because of its high morbidity and mortality. One of the critical factors in the spread of diarrhea is food and drink hygiene. This study aims to determine the application of food sanitation and hygiene (FSH) in families with diarrhea sufferers. The research was conducted from June to November 2021 using quantitative methods with a descriptive design. Thirty families selected purposively were involved in the study with the criteria of having diarrhea (January to April 2021), taking treatment, and living in the Puskesmas Rajabasa Indah working area. Data were collected by observing the implementation of food sanitation hygiene and examining food samples. All data were analyzed descriptively and presented as a frequency table. The results showed that 63.3% of the food consumed was contaminated with microorganisms, and only 13.3% applied food sanitation hygiene. 83.3% and 43.3% of households choose and store food ingredients properly. However, only 13.3% of households process food well. Meanwhile, the proportions that store and present well are 43.3% and 73.3%. This study has shown that the application of FSH in families with cases of diarrhea is still poor—increasing knowledge through campaigns is urgent to implement.